1996
DOI: 10.1182/blood.v87.6.2401.bloodjournal8762401
|View full text |Cite
|
Sign up to set email alerts
|

Increased activity and sensitivity of mitochondrial respiratory enzymes to tumor necrosis factor alpha-mediated inhibition is associated with increased cytotoxicity in drug-resistant leukemic cell lines

Abstract: The drug-resistant leukemic cell lines, CEM/VLB100 and K/DAU600, are more sensitive to tumor necrosis factor alpha (TNFalpha)-mediated cytotoxicity compared with their parental cell lines, CCRF-CEM and K562 cl.6. Drug-resistant leukemic cell lines have more active mitochondrial function, which is associated with a greater susceptibility to TNFalpha- induced respiratory inhibition. TNFalpha blocked electron transfer at three sites, NADH dehydrogenase (complex I), succinate dehydrogenase (complex II), and cytoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
36
2

Year Published

1997
1997
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 22 publications
1
36
2
Order By: Relevance
“…1% Triton-X 100. The LDH activity was determined using a LDH assay kit (Amador et al, 1963;Jia et al, 1996).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…1% Triton-X 100. The LDH activity was determined using a LDH assay kit (Amador et al, 1963;Jia et al, 1996).…”
Section: Methodsmentioning
confidence: 99%
“…Oxygen consumption was calibrated with air-saturated respiratory medium, assuming 390 ng atoms O 2 /ml. Respiratory rate or enzyme activity was expressed in ng atoms O 2 /min/10 7 cells (Granger & Lehninger, 1982;Schoonen et al, 1990;Jia et al, 1996).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies in our department have found that MDR1-positive leukaemia cells CEM/VLB100 and K562/ Dau600 were more sensitive to TNF-induced cell killing than their parental cell lines (Jia et al, 1995(Jia et al, , 1996. Although these were related in part to decreased manganese superoxide dismutase (MnSOD) activity and increased activity in the enzymes of the mitochondrial electron transport chain in drug-resistant cell lines (Jia et al, 1997), the mechanisms and the signalling pathways related to these is still unclear.…”
mentioning
confidence: 99%